Use of Word Wall Learning Media to Improve Learning Outcomes Indonesian Learning in Elementary Schools - Elhefni Elhefni; Al Ihwanah Al Ihwanah; Helen Sabera Adib; Rita Ariani; Ria Safitri (AL-ISHLAH: Jurnal Pendidikan, 2023)
One educational component that can aid in producing excellent learning results is the use of learning media. In Indonesia, word walls are used as a form of educational media as part of a larger attempt to boost learning outcomes for students. The purpose of this research is to find out how using word walls as a teaching tool for the Indonesian language affects the academic performance of primary school pupils in Palembang. The methodology of this investigation was quantitative. This study employed a pre-experimental design as its research methodology, which is an experimental approach. This study employed a single-group pre- and post-test research design. Thirty-three third-graders made up the study's sample. Tests are used to acquire data. T-tests are used as the approach for analysing the data. First, the average score was 56 on the test before using the word wall as a learning tool. Second, the average score after using word wall learning media is 70. Third, the t-test shows that the count t is greater than the table t (3.546 2.037). Thus, it can be concluded that there are significant differences in student learning outcomes in learning Indonesian before and after the use of word wall learning media. This study recommends teachers to use word walls in Indonesian learning as an alternative to existing learning media